2017
DOI: 10.1016/j.athoracsur.2016.08.110
|View full text |Cite
|
Sign up to set email alerts
|

Fontan Patient Survival After Pediatric Heart Transplantation Has Improved in the Current Era

Abstract: Survival of Fontan patients after HT has significantly improved in the current era. Currently, expected post-HT survival for Fontan patients is on par with other CHD patients. Fontan patients should not be excluded from consideration for HT solely on a history of Fontan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 17 publications
2
52
1
Order By: Relevance
“…Although this may have contributed to the trend toward decreased waitlist mortality among all CHD candidates, we surmise that these changes were secondary to changes in management of the CHD population over time rather than as a result of the criteria revision. For example, there has been increased emphasis in the last decade on care of the Fontan patient, including recommendations to consider earlier transplant evaluation referral . This is supported by the greater listing rate we observed for CHD but not CM candidates in Era 2.…”
Section: Discussionmentioning
confidence: 63%
“…Although this may have contributed to the trend toward decreased waitlist mortality among all CHD candidates, we surmise that these changes were secondary to changes in management of the CHD population over time rather than as a result of the criteria revision. For example, there has been increased emphasis in the last decade on care of the Fontan patient, including recommendations to consider earlier transplant evaluation referral . This is supported by the greater listing rate we observed for CHD but not CM candidates in Era 2.…”
Section: Discussionmentioning
confidence: 63%
“…When looking at 402 Fontan patients (<18 years of age) who underwent heart transplant—patients in the early era of transplant (1993‐2006) had a 1‐year post‐transplant survival of 77% and a more contemporary era (2007‐2014) had a 1‐year post‐transplant survival of 89%. In this same 2007‐2014 era, the 1‐year post‐transplant survival for non‐Fontan CHD was 92% …”
Section: Introductionmentioning
confidence: 95%
“…Previously reported outcomes following heart transplantation in the Fontan population have been poor, but recent analyses by Simpson et al demonstrate improved one‐year survival . Lamour et al (2009) reported a 1‐year post‐transplant survival of 71% in Fontan patients and 83% in non‐Fontan congenital heart disease (CHD) patients .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent interrogation of the Paediatric Heart Transplant Study Database showed improved 1-year survival from 71% [1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006] to 89% [2007][2008][2009][2010][2011][2012][2013][2014] for those undergoing OHT for FFP, reaching comparable outcomes to other CHD patients (42). Other paediatric registry data has shown comparable outcomes between Fontan and nonFontan SV OHT patients (27,43,44).…”
Section: Mortality In Sv Heart Transplantationmentioning
confidence: 99%